2018
DOI: 10.1589/jpts.30.96
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of manual therapy in treating cervicogenic dizziness: a systematic review

Abstract: [Purpose] This review provides an evaluation of the evidence for the effectiveness of using manual therapy to treat cervicogenic dizziness. [Subjects and Methods] The literature was systematically searched on the May 2, 2016 using the following online databases: Medline, EMBASE, CINAHL and PEDro. This review included randomised controlled trials and compared the efficacy of manual therapy for the treatment of cervicogenic dizziness, compared to other types of intervention. This study measured changes based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Maitland passive mobilizations and Mulligan SNAGs did not produce a significant difference in intensity of dizziness when compared to placebo after 12 months; however, there was a significant difference in frequency of dizziness and DHI for both passive mobilizations and SNAGs [18]. The systematic reviews by Reid [6] and Yaseen [8] both suggest that there is a need for higher quality evidence to inform the use of manual therapy as a treatment technique for CGD, and Lystad et al [14] recommends further researching manual therapy in conjunction with vestibular rehabilitation as a possible treatment for CGD.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Maitland passive mobilizations and Mulligan SNAGs did not produce a significant difference in intensity of dizziness when compared to placebo after 12 months; however, there was a significant difference in frequency of dizziness and DHI for both passive mobilizations and SNAGs [18]. The systematic reviews by Reid [6] and Yaseen [8] both suggest that there is a need for higher quality evidence to inform the use of manual therapy as a treatment technique for CGD, and Lystad et al [14] recommends further researching manual therapy in conjunction with vestibular rehabilitation as a possible treatment for CGD.…”
Section: Introductionmentioning
confidence: 93%
“…Cervicogenic dizziness can result in a variety of coexisting symptoms such as unsteadiness, lightheadedness, perceptions of spinning, nausea, and general disorientation [8]. Thompson-Harvey and Hain reported that patients with cervical vertigo have neck pain (94%), true vertigo (27%), and headache (50%) [9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations